MOTS-c repairs myocardial damage by inhibiting the CCN1/ERK1/2/EGR1 pathway in diabetic rats - Wang, Manda; Wang, Gangqiang; Pang, Xiaoli; Ma, Jiacheng; Yuan, Jinghan; Pan, Yanrong; Fu, Yu; Laher, Ismail; Li, Shunchang (Frontiers in Nutrition, 2023)
Cardiac structure remodeling and dysfunction are common complications of diabetes, often leading to serious cardiovascular events. MOTS-c, a mitochondria-derived peptide, regulates metabolic homeostasis by accelerating glucose uptake and improving insulin sensitivity. Plasma levels of MOTS-c are decreased in patients with diabetes. MOTS-c can improve vascular endothelial function, making it a novel therapeutic target for the cardiovascular complications of diabetes. We investigated the effects of MOTS-c on cardiac structure and function and analyzed transcriptomic characteristics in diabetic rats. Our results indicate that treatment with MOTS-c for 8-week repaired myocardial damage and preserved cardiac systolic and diastolic function, Transcriptomic analysis revealed that MOTS-c altered 47 disease causing genes. Functional enrichment analysis indicated MOTS-c attenuated diabetic heart disease involved apoptosis, immunoregulation, angiogenesis and fatty acid metabolism. Moreover, MOTS-c reduced myocardial apoptosis by downregulating CCN1 genes and thereby inhibiting the activation of ERK1/2 and the expression of its downstream EGR1 gene. Our findings identify potential therapeutic targets for the treatment of T2D and diabetic cardiomyopathy.